Sirtuin 2 Regulates Microvascular Inflammation during Sepsis - Nancy Buechler; Xianfeng Wang; Barbara K. Yoza; Charles E. McCall; Vidula Vachharajani (Journal of Immunology Research)
Objective. Sepsis and septic shock, the leading causes of death in noncoronary intensive care units, kill more than 200,000/year in the US alone. Circulating cell-endothelial cell interactions are the rate determining factor in sepsis inflammation. Sirtuin, a seven-member family of proteins (SIRT1–7), epigenetically controls inflammation. We have studied the roles of SIRTs 1, 3, and 6 in sepsis previously. In this project, we studied the role of SIRT2 on sepsis-related inflammation. Methods. Sepsis was induced in C57Bl/6 (WT), SIRT2 knockout (SIRT2KO), and SIRT2 overexpressing (SIRT2KI) mice by cecal ligation and puncture (CLP). We studied leukocyte/platelet adhesion using intravital microscopy and E-selectin/ICAM-1 adhesion molecule expression in the small intestine with immunohistochemistry (IHC) six hours post-CLP/sham surgery. We also studied 7-day survival rates in WT, SIRT2KO, and SIRT2KI sepsis mice. Results. Compared to WT mice, SIRT2KO mice show exaggeration while SIRT2KI mice show attenuation of cellular adhesion with sepsis in the small intestine. We also show that the small intestinal E-selectin and ICAM-1 expressions increased in SIRT2KO and decreased in SIRT2KI mice versus those in WT sepsis mice. We show that the 7-day survival rate is decreased in SIRT2KO and increased in SIRT2KI sepsis mice. Conclusion. SIRT2 modulates microvascular inflammation in sepsis and affects survival.